The Comprehensive Infrequency/Frequency Item Repository (CIFR): An online database of items for detecting careless/insufficient-effort responders in survey data. (April 2023) - Kay, Cameron S.; Saucier, Gerard
Abstract: A promising method for detecting careless or insufficient effort (C/IE) responders is the infrequency/frequency-item method. Infrequency items are items that should be endorsed by almost no one (e.g., "I like being frustrated") and frequency items are items that should be endorsed by almost everyone (e.g., "I keep some of my thoughts to myself"). Participants are flagged as C/IE responders if they tend to agree with the infrequency items and tend to disagree with the frequency items. Here, we introduce the Comprehensive Infrequency / Frequency Item Repository (CIFR)—an online database of 660 infrequency/frequency items. The purpose of CIFR is to provide researchers with a tool for selecting infrequency/frequency items that are not only valid but also match the content of the other items in their surveys. An initial validation effort based on 1166 participants indicated that most of the infrequency items in CIFR are, in fact, infrequent, and most of the frequency items in CIFR are, in fact, frequent. Although additional validation work is necessary, the present results indicate that CIFR can be a valuable tool for researchers who wish to ensure the quality of their data.